Third Consecutive La Niña? What to Expect from Soybean Yields in the United States, Brazil and Argentina - Cabrini, Silvina María (2022)
International long-term forecast models hint at the possibility of a third consecutive La Niña event this year. It is not uncommon to see La Niña occurring over two successive seasons. This happened in both 2021-2022 and 2011-2012. However, it is rare to see three consecutive La Niña events. But what could this mean for soybean production in Brazil, the United States, and Argentina? This article presents descriptive analyses of deviations from the trendline of soybean yields over the last 30 years in these countries, the three largest producers and exporters of soybeans in the world, to predict what to expect from soybean yields this year. Although, the strength of individual La Niña events and various climate factors make each event unique.